Increased Incidence of Thyroid Dysfunction and Autoimmunity in Patients with Vernal Keratoconjunctivitis - Stefano Stagi; Neri Pucci; Laura Di Grande; Cinzia de Libero; Roberto Caputo; Stefano Pantano; Ivan Mattei; Francesca Mori; Maurizio de Martino; Elio Novembre (International Journal of Endocrinology)
Hormones may play a role in the pathophysiology of vernal keratoconjunctivitis (VKC). An increased incidence of thyroid autoantibodies was recently observed in VKC, although there were no data on thyroid function. Two hundred and eighty-eight patients (202 males, 86 females; range 5.5 to 16.9 years) with VKC were evaluated and compared with 188 normal age- and sex-matched subjects. In all subjects, serum concentrations of free T4, TSH, thyroperoxidase, thyroglobulin, and TSHr autoantibodies were evaluated. In VKC, the family history of thyroid diseases showed no significant differences compared to the controls (9.4 versus 8.6%), whereas the family history of autoimmune diseases was significantly higher (13.2% versus 6.3%; P<0.05). Subclinical hypothyroidism was diagnosed in 6.6% (versus 1.6% of the controls; P<0.05) and overt hypothyroidism in 0.7% (versus 0.0% of the controls; P=NS). Finally, 5.2% of patients were positive for thyroid autoantibodies, which were significantly higher with respect to the controls (0.5%, P<0.05). In the patients positive for thyroid autoantibodies, 80% showed a sonography pattern that suggested autoimmune thyroiditis. Thyroid function and autoimmunity abnormalities are frequently present in children with VKC. Children with VKC should be screened for thyroid function and evaluated for thyroid autoimmunity.